Survey of currency derivative usage by Indian SMEs / N. Mukund Sharma - Sharma, N. Mukund (2011)
This paper reports the results of a cross-sectional survey of the currency derivative usage by SMEs (Small and Medium enterprises) in India. The study was undertaken with the objective of studying the nature and extent of currency derivative usage by Indian SMEs and to understand the motive behind the usage of currency derivatives. This study is based on the primary data provided by 80 SMEs. The findings of the survey are in line with the expectation. More than half of respondents do not use currency derivatives in managing their currency exposure and prime reason for the same is high cost associated with derivative usage. Even those respondent SMEs who make use of derivative are mainly dependent on Forward contract and usage of other derivative product is trivial. The main reason behind non usage of Futures, Option Swaps and other structured products is that the above said products are not offered by the banks with whom they normally deal. This is due to the fact that most of the SMEs deal with Nationalised Public sector banks which do not offer and encourage the usage of the above said derivative products due to wide ranging reasons.